ANALISIS REALISASI ANGGARAN BELANJA PADA BALAI PENGELOLAAN DAERAH ALIRAN SUNGAI DAN HUTAN LINDUNG KETAHUN BENGKULU DENGAN MENGGUNAKAN METODE VALUE FOR MONEYANALISIS REALISASI ANGGARAN BELANJA PADA BALAI PENGELOLAAN DAERAH ALIRAN SUNGAI DAN HUTAN LINDUNG K - Pedi Riswandi Riswandi (Universitas Prof.Hazairin,SH Bengkulu, 2018)
This study aims: (1) to know the economic level of budget realization; (2) to know the level of effectiveness of budget realization; (3) to know the level of efficiency of expenditure realization at River Basin Management and Bengkulu Ketahun Protected Forest. The results of the analysis on the Realization of Expenditure Budget at the Management Center of Watershed and Protection Forest of Bengkulu Year by using Value for Money Methods show that (1) In terms of economic aspect, the realiation of budget at River Basin Management and Bengkulu Ketahun Protected Forest, 2014 runs quite economically. As for the year 2015 the realization of expenditure budget at River Basin Management and Bengkulu Ketahun Protected Forest runs economically. Then for the year 2016 budget realization at the River Basin Management and Bengkulu Ketahun Protected Areas runs less economical, due to self-blocking budget by the government. (2) Judging from the aspect of efficiency, the realiation of budget at River Basin Management and Bengkulu Ketahun Protected Forest, in 2014-2016 runs very efficiently. (3) Judging from the aspect of effectiveness, the realiation of budget at River Basin Management and Bengkulu Ketahun Protected Forest, in 2014 is quite effective. As for the year 2015 and 2016 the realization of expenditure budget at the Management Hall of River Basin and Bengkulu Ketahun Protected Forest run effectively